Gambaran Tingkat Demensia pada Lansia di Rojinhome Ikedaen Okinawa Jepang - Nabila, Bangkit Isna; Kurniawan, Wasis Eko; Maryoto, Madyo (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The aging process in the elderly can be divided into three stages, namely weakening of function, functional limitations, disabilities, and handicaps that arise as a result of this decline. The cognitive or intellectual system, namely dementia, is one of the body systems that experience decline. Dementia is a condition of progressive intellectual decline that affects cognitive and functional abilities. Dementia has a detrimental effect on the elderly if not treated immediately, including changes in the patient's behavior such as forgetting who he is, and the elderly who wander alone to a location are likely to get lost because they do not remember the direction home. The brains of older adults with dementia are found to be damaged, with cell death and loss of blood supply to the brain. The aim of this study was to determine the prevalence of senility in the elderly at Rojinhome Ikadaen, Okinawa. The magnitude of senility in the elderly in fulfilling daily activities was described using quantitative and descriptive methods in this study. Most of the older women (75-90 years old) had a history of hypertension, and most had moderate dementia. The elderly are required to be able to perform regular physical activities, ranging from low-intensity activities such as meeting daily needs to moderate-intensity activities such as participating in the orphanage gymnastics program to improve cognitive function.